Exploration of Zamzam Water Consumption on Toddlers' Expressive Language Abilities: A Review from Islamic and Psycholinguistic Perspectives - Trisna, Ayu; Pasaribu, Usrawati; Apripan, Rika; Handayani, Fitri Rahma; Siregar, Mariani (Universitas Pahlawan Tuanku Tambusai, 2026)
Expressive language skills are a crucial aspect of toddler development, because they are directly related to communication, social understanding, and learning readiness. Toddlerhood is the golden period in which appropriate stimulation significantly supports optimal language development. In Padangsidimpuan City, Zamzam water is better known as holy water consumed in the context of Hajj and Umrah pilgrimages. Its use in supporting child development, especially language development, is not yet a common practice. By highlighting this local context, this study is important to open new horizons where religious beliefs can be integrated with a psycholinguistic approach to support child growth and development, including language. This study aimed to explore the practice and meaning of Zamzam water consumption by parents in supporting toddlers' expressive language skills, viewed from an Islamic and psycholinguistic perspective. Using a qualitative approach with a case study method, data were obtained through in-depth interviews, observations, and documentation, and then analyzed thematically. The results showed that providing Zamzam water twice a day for three months with accompanying prayers and verbal interactions demonstrated expressive language development through simple basic vocabulary. These findings indicate that Zamzam water consumption influences toddlers' language development through aspects of family spirituality that improve the quality of verbal interactions, thereby stimulating toddlers' expressive language.